Modelling Acid-Rock Interactions and Mineral Dissolution During RMA Stimulation Test Performed at the Soultz-sous-Forêts EGS Site, France - Portier, Sandrine; Vuataz, François (My University, 2010)
The Soultz EGS reservoir’s response to chemical stimulation is assessed by numerical simulation of coupled thermo-hydraulic-chemical processes. To assess chemical interactions between host rocks and a mixture of HCl and HF as well as its potential effects on the Soultz EGS reservoir, new modelling efforts using the FRACHEM code have been initiated. This paper presents the model calibration and results. Simulations consider realistic conditions with available data sets from the EGS system at Soultz. Results indicate that the predicted amount of fracture sealing minerals dissolved by injection of a mixture of acids (RMA) was consistent with the estimated amount from the test performed on GPK4 well at Soultz EGS site. Consequently reservoir porosity and permeability can be enhanced especially near the injection well by acidizing treatment.
Keywords: Regular Mud Acid; chemical stimulation; fractured granite; secondary minerals; thermo-hydraulic-chemical coupled code; acid-rock interactions; acid mineral reaction rates; porosity; permeability; Enhanced Geothermal System (EGS); Soultz-sous-Forêts